ECONOMICS OF TOURISM INDUSTRY ENTERPRISES: PROBLEMS AND PROSPECTS OF DEVELOPMENT - ZHURBA, Igor; NESTORISHEN, Ihor; MATYUKH, Serhiy (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The authors of the study analyzed the current state and prospects of development of the tourism industry in Ukraine and the world. The authors note that in the conditions of military aggression of the Russian Federation Ukraine suffers significant economic, financial and social losses. According to many experts, Ukraine's economy expects a significant reduction (approximately 30-45%) of GDP. In addition, due to the significant level of globalization of the international economy and the close economic interconnections of economic systems of national economies, there will be a significant decline (decline) in economic development not only in Eastern Europe but in the world as a whole. Thus, today the issues of directions of economic recovery of Ukraine's economic potential, as well as the place and role of the tourism industry in the postwar recovery of the domestic economy are becoming increasingly important in Ukraine.The purpose of the study is to develop guidelines for the systematization of risk factors for domestic tourism, as well as to determine the directions and vectors of the restoration of the tourism business in Ukraine in the postwar period.The authors of the study noted that according to the World Tourism Organization (UNWTO), tourism is one of the most dynamic sectors of global exports in the world. The average annual growth rate of the global tourism industry averaged about 5% per year. By 2022, tourism provided up to 10% of gross world income and every tenth job in the world is directly or indirectly generated by tourism. However, the global crisis caused by the COVID-19 pandemic has destroyed the economy of the tourism sector, leading to unprecedented consequences for jobs and businesses. The current crisis has also revealed some shortcomings in the management and readiness of the industry, as well as in the ability to respond to current challenges and threats. Restoring the confidence of tourists and participants in the tourism chain, stimulating demand and accelerating the resumption of tourism urgently requires political action at the national and international levels, as well as improved coordination. The crisis is an opportunity to rethink the development of tourism. Recovery should include transforming the sector, changing tourism destinations, transforming the tourism ecosystem, bringing innovation and investing in sustainable tourism. The authors have formed measures to restore the tourism sector in the world.The study analyzes domestic trends in the development of the domestic industry in the prewar period, identified new trends in the geography of foreign tourists, as well as summarizes the directions of recovery of the domestic tourism sector.
Keywords: tourism; tourism economy; Ukraine; Be brave like Ukraine; COVID-19